2022
DOI: 10.1001/jamanetworkopen.2022.22390
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Release of Patients After Treatment in an Anesthesiologist-Staffed Mobile Emergency Care Unit

Abstract: IMPORTANCEPrehospital treatment and release of patients may reduce unnecessary transports to the hospital and may improve patient satisfaction. However, the safety of patients should be paramount. OBJECTIVE To determine the extent of unplanned emergency department (ED) contacts, shortterm mortality, and diagnostic patterns in patients treated and released by a prehospital anesthesiologist supervising a mobile emergency care unit (MECU). DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…Among non-conveyed patients, the crude mortality rate was 2%. Despite variations in conditions, dispatch priory level and time intervals of outcomes, the mortality rate observed in this study aligns with comparable studies, wherein reported mortality rates have ranged from 0 to 2.3% [6,11,12,23]. Yet, the adjusted risk of mortality within non-conveyed patients was significantly higher compared to conveyed patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Among non-conveyed patients, the crude mortality rate was 2%. Despite variations in conditions, dispatch priory level and time intervals of outcomes, the mortality rate observed in this study aligns with comparable studies, wherein reported mortality rates have ranged from 0 to 2.3% [6,11,12,23]. Yet, the adjusted risk of mortality within non-conveyed patients was significantly higher compared to conveyed patients.…”
Section: Discussionsupporting
confidence: 81%
“…Yet, the adjusted risk of mortality within non-conveyed patients was significantly higher compared to conveyed patients. This could be explained by the unknown proportion of patients declared terminally ill within the non-conveyed cohort [12]. Nonetheless, this finding stresses the need for additional research to ascertain possible confounders and risk factors associated with this correlation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To standardize the clinical presentations in prehospital critical care, novel scoring systems have been proposed to evaluate and predict the risk of early clinical worsening [ 3 ]. Currently, precision medicine has made great strides in improving prehospital care and emergency departments (EDs), providing bedside scores composed of various clinical, physiological, comorbidity-related, and/or analytical variables as invaluable support in the decision-making process [ 4 ].…”
Section: Introductionmentioning
confidence: 99%